Indicators of Effective Use of Assessment Feedback in Undergraduate Writing Courses - Tavakolian, Shahrzad; Rahbarian, Behnam (Assessment and Practice in Educational Sciences, 2024)
This study aims to identify the key indicators that characterize the effective use of assessment feedback in undergraduate writing courses, as perceived by students and instructors. A qualitative research design was employed, utilizing semi-structured interviews with 21 participants (students and instructors) from undergraduate writing courses in Tehran. Participants were selected through purposive sampling to capture a range of experiences with assessment feedback. Interviews were conducted until theoretical saturation was achieved, and each was audio-recorded, transcribed, and analyzed thematically. NVivo software was used to support systematic coding and the identification of main themes and subthemes. Analysis revealed three major themes with several subcategories as indicators of effective feedback use: (1) feedback reception and understanding, including clarity, timeliness, engagement, emotional response, accessibility, and growth orientation; (2) feedback utilization and application, such as integration into revisions, self-regulation skills, feedback-seeking behaviors, transferability across tasks, and barriers to utilization; and (3) instructor practices and institutional support, encompassing consistency, alignment with learning outcomes, feedback dialogue, professional development, supportive policies, recognition, and access to resources. Illustrative quotations highlighted the importance of clear, timely, actionable, and dialogic feedback, as well as the necessity of institutional and instructor support to overcome barriers and foster meaningful engagement with feedback. Effective use of assessment feedback in undergraduate writing courses depends on a complex interplay of clear communication, emotional support, proactive student engagement, and robust institutional and instructor practices. The identified indicators provide a comprehensive framework for improving feedback processes, supporting student development, and informing professional development and policy at the course and institutional level.